2021
DOI: 10.30605/onoma.v7i1.448
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Lexical Cohesion on Indonesian Singer Song

Abstract: This paper sheds light on investigating the lexical cohesion on an Indonesian singer song entitled Coke Bottle by Agnez Mo. Lexical cohesion constitutes linguistic devices that help to create cohesiveness of the text. Lexical cohesion occurs when two words or more in a text are semantically related somehow – in other words, they are related in terms of their meaning. This study's design was a descriptive qualitative that attempted to elaborate the discourse analysis about lexical cohesion in Coke Bottle song b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The findings also indicated that repetition has made the song deeper and increased the emotion of the hearer. A similar finding was shown in the study by Murodi, Hidayat, and Alek (2021) when they analyse the lexical cohesion of the song. They found that repetition was mostly used in the songs.…”
Section: Studies On Grammatical and Lexical Cohesionsupporting
confidence: 87%
See 2 more Smart Citations
“…The findings also indicated that repetition has made the song deeper and increased the emotion of the hearer. A similar finding was shown in the study by Murodi, Hidayat, and Alek (2021) when they analyse the lexical cohesion of the song. They found that repetition was mostly used in the songs.…”
Section: Studies On Grammatical and Lexical Cohesionsupporting
confidence: 87%
“…Most studies have been focused on the analysis of grammatical and lexical cohesion in song lyrics (e.g. Murodi et al, 2021;Putri, 2022;Sari & Anindita, 2020;Sholah, & Yunus, 2020;Telaumbanua, 2021). For example, Sholah and Yunus (2020) conducted a study that focuses on the lexical and grammatical cohesion in a song by adapting Halliday and Hasan`s (1976) lexical cohesion model.…”
Section: Studies On Grammatical and Lexical Cohesionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with these ideas, Yuwono in the book entitled Pesona bahasa langkah awal memahami linguistik (The charm of language is the first step to understanding linguistics) in 2005 also adds that lexical cohesion is an inter-semantic relationship forming discourse by utilizing lexical elements or words. Then Murodi, Hidayat, and Alek (2021), Sari, Mujiyanto, and Rukmini (2022), and as explained by Halliday & Hasan in the book entitled Cohesion in English in 1976 that lexical cohesion can be achieved through reiteration and collocation. Reiteration includes repetition, synonymy, antonymy, and hyponymy.…”
Section: Introductionmentioning
confidence: 98%
“…Lexical cohesion is concerned with the relationships that exist between lexical items in a text, such as words and phrases. Lexical cohesion occurs when two or more words are in a text (Murodi et al, 2021). Thus, cohesion plays an significant role in arranging parts of the text according to the situation (Sujatna et al, 2021).…”
Section: Introductionmentioning
confidence: 99%